HUBUNGAN DISIPLIN DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA SELAMA PEMBELAJARAN DARING KELAS VI B SD 1 MIJEN - Rahmawati, Annisa; Masfuah, Siti; Khamdun, Khamdun (Universitas Muria Kudus, 2021)
The purpose of this study was to analyze how much the relationship between discipline and student learning outcomes in science subjects class VI B SD 1 Mijen during online learning. This research uses quantitative research methods with a correlation test.This research will be conducted in class VI B SD 1 Mijen with 26 students as research subjects. The sampling technique in this research is usingtechnique purposive random sampling. The sample in this study amounted to 26 students. The independent variable in this study was student learning discipline, while the dependent variable in this study was student learning outcomes. Data collection techniques in this study used a questionnaire instrument and document study from the classroom teacher in the form of student learning outcomes in science subjects. The data analysis technique in this study used a correlation test of the discipline relationship with science learning outcomes. The results of this study indicate that there is a disciplinary relationship with science learning outcomes during online learning with a correlation value of 0.6512 in the strong category.